The Application of the Sorogan and Takrir Methods in Increasing Understanding of Arabic Texts - Muhamad Ardha Niami; Abdul Qodir (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2023)
Learning is a process in which a person changes his behavior as a result of experience. Therefore, researchers are interested in researching the Institute of Youth Education, Pacul Gowang Jombang. The focus of research in writing this thesis is: (1) How is Surugan Takreer applied in the Youth Education Institute? (2) How do students at the Institute for Youth Education understand Arabic texts? (3) What are the motives and obstacles in applying Surugan Takreer to increase Arabic texts in the Youth Education Institute? The type of research used is descriptive qualitative research. The study data collection techniques used are observation, interviews and in-depth documentation. While analyzing the data used are Miles and Hubermin's theory which is data reduction, data presentation and conclusion. This study also validated the data with expanded participation, continued monitoring, and triangulation of sources and techniques. The search result is (1) Applying the Surugan and Takreer method through the Yellow Book (a) The purpose of using the Surugan and Takreer method will be easier to justify if there are errors. In reading Arabic texts in the Yellow Book (B) Preparation for learning to read Arabic texts by nderes first before Surujan. (c) In practice, students read in front of the teacher and the teacher listens while making corrections. Advantages of the Surujan method: (a) The objectivity of this method, in addition to facilitating reading, is more important for preserving and preserving the reading that the reader possesses (b) Preparing for learning to read the Yellow Book by the repeating method, that is, repeating the reading until it is completely memorized. (c) Application of learning to read Arabic texts in the yellow book, i.e. students present their reading before the teacher so that the teacher can justify if there is an error in the reading. (d) Evaluation is carried out by bringing evidence of stored reading, at which time the teacher gives grades.